2000
DOI: 10.1002/(sici)1099-0992(200001/02)30:1<101::aid-ejsp979>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Learning to play golf under different goal conditions: their effects on irrelevant thoughts and on subsequent control strategies

Abstract: Volitional and self‐handicapping theories suggest that individuals use various strategies to energize the maintenance and the enactment of goals. We placed 32 golfers (16 men and 16 women) alternately in four golf proficiency conditions using a randomized complete block design: task involvement, learning, achievement, and one‐on‐one competition goals. As expected, the path analysis showed that one‐on‐one competition goals generate irrelevant thoughts (anxiety, threat to self‐esteem, distraction) as well as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 52 publications
1
15
0
3
Order By: Relevance
“…State anxiety. Thill and Cury's (2000) four-item measure (Appendix C) was used to assess state anxiety.…”
Section: Methodsmentioning
confidence: 99%
“…State anxiety. Thill and Cury's (2000) four-item measure (Appendix C) was used to assess state anxiety.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, integrative studies used one or two of the above factors in a context of a golf performance (Beauchamp P., et al, 1996;Beauchamp M., et al., 2002;Catley & Duda, 1997;Cumming, Hall, Harwood, & Gammage, 2002;Gaudreau & Blondin, 2004a, 2004bGaudreau et al, 2002;Thill & Cury, 2000). Two studies can be distinguished because of their use of an experimental design (Beauchamp et al, 1996;Thill & Cury, 2000). Beauchamp et al (1996) examined the effect of a 14-week golf-teaching program on the motivation, preparation, and putting performance of novice golfers.…”
Section: Psychological Factors Related To Golf Performancementioning
confidence: 99%
“…The results indicated that the cognitive-behavioral group presented higher levels of intrinsic motivation, a more consistent use of preputt routines and better putting performance as compared with the 2 other groups. Thill and Cury (2000) used a similar design with recreational golfers and found that a motivational context of one-on-one competition leads to anxiety and distraction, whereas a taskinvolving context excludes intrusive thoughts and is negatively related with selfhandicapping. Using a correlational design with a sample of recreational golfers, Catley and Duda (1997) studied the psychological antecedents of flow and found that preround measure readiness variables (calm, positive focus, confident readiness and pessimism) as well as golf skill level were significantly related to the frequency and intensity of flow.…”
Section: Psychological Factors Related To Golf Performancementioning
confidence: 99%
“…A study by Thill and Cury (2000) may shed light on why such differences failed to emerge. The authors found social comparison goals (similar to performance-approach goals) to be associated with greater distraction and anxiety during a task and the utilization of strategies to control intrusive thoughts.…”
Section: Discussionmentioning
confidence: 99%